SISTEM PENDUKUNG KEPUTUSAN TENDER PROYEK INFRASTRUKTUR JARINGAN KOMPUTER UPTD SMA 3 TEGAL DENGAN METODE BENEFIT COST RATIO (BCR) - Haries Anom Susetyo Aji Nugroho; Khoirul Mustofa (Universitas Sebelas Maret, 2017)
Procurement process of computer network infrastructure is one of the critical aspects for bussiness process UPTD SMA 3 Tegal. Way of the procuremen process is by project tender. Aim of project tender is budget efficiency UPTD SMA 3 Tegal. One of company will submit a proposal with the excess of the price and profit of them. For make it easier then a tool is needed, it is Decision Support System (DSS) by method a Benefit Cost Ratio (BCR). File of tender entered on this system is file of company,company address, owner name, type of tender, bid price and many more documents have been verified by admin of this decision support system. Output from this decision support system is acompany’s name of the winner of the tender of computer network infrastructure base on benefit cost ratio (BCR) method that has been applied to desicion support system.